The Therapeutic Effect of Second Near-Infrared Absorbing Gold Nanorods on Metastatic Lymph Nodes via Lymphatic Delivery System - Adewale O. Oladipo; Thabang C. Lebepe; Vuyelwa Ncapayi; Ncediwe Tsolekile; Sundararajan Parani; Sandile P. Songca; Shiro Mori; Tetsuya Kodama; Oluwatobi S. Oluwafemi (MDPI AG, 2021)
Photothermal therapy has been established recently as a non-invasive treatment protocol for cancer metastatic lymph nodes. Although this treatment approach shows efficient tumour ablation towards lymph node metastasis, the monitoring and reporting of treatment progress using the lymphatic delivery channel still need to be explored. Herein, we investigated the anti-tumour effect of pegylated gold nanorods with a high aspect ratio (PAuNRs) delivered via the lymphatic route in a mouse model. In this study, breast carcinoma (FM3A-Luc) cells were inoculated in the subiliac lymph node (SiLN) to induce metastasis in the proper axillary lymph node (PALN). The treatment was initiated by injecting the PAuNRs into the accessory axillary lymph node (AALN) after tumour metastasis was confirmed in the PALN followed by external NIR laser irradiation under a temperature-controlled cooling system. The anti-tumour impact of the treatment was evaluated using an in vivo bioluminescence imaging system (IVIS). The results showed a time-dependent reduction in tumour activity with significant treatment response. Tumour growth was inhibited in all mice treated with PAuNRs under laser irradiation; results were statistically significant (** p < 0.01) even after treatment was concluded on day 3. We believe that this non-invasive technique would provide more information on the dynamics of tumour therapy using the lymphatically administered route in preclinical studies.